Aspek Perpajakan Pada Pajak Penghasilan Bumdes Sinar Usaha Desa Budo, Kecamatan Wori Kabupaten Minahasa Utara - Heidy Pesik; Johanes H Tene; Mawar Domits (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Negeri Manado, 2022)
Village-Owned Enterprises as a form of business entity used to manage businesses or utilize village assets with the aim of improving the welfare of the Village community as of last year 2021 based on the latest law for Village Owned Entererprises PP no 11 of 2021 already has its own legal entity status. With this affirmation, BumDes has a tax obligation as a legal entity that earns income. In the case of Village Owned Enterprises tax obligations, it is the same as calculating taxes for corporate taxpayers. To further improve knowledge and good and correct taxation procedures based on applicable laws, we provide knowledge to village communities and Village-Owned Enterprises management to be able to understand the procedures for calculating, depositing and reporting Taxes in this case Corporate Taxpayer Income Tax. Because with taxes we can participate build the nation and state as part of a good citizen. The response from the Village-Owned Enterprises Management and the Budo Village community was extraordinary, marked by the many questions during the discussion. But the most important thing is the form of implementation of this is that the Sinar Usaha Village-Owned Enterprises is improving in terms of Village-Owned Enterprises administration that supports the achievement of correct tax reporting. Where in previous practice due to lack of understanding, it has not run smoothly for tax reporting. It is hoped that this will have a significant impact on the pioneering of correct and timely income tax.